c.1 - "Asthana, M.D.(ed.)" (New Delhi, 2001)
The 26 papers collected in this volume come from a seminar organized in April, 2001 in New Delhi jointly by the Planning Commission, Government of India, the United Nations World Food Programme and M.S. Swaminathan Research Foundation. The papers throw light on the possibilities for achieving freedom from hunger in India by 2007. While emphasizng the need to give women a pivotal role in economic activities, the papers also focus on extending opportunities of sustainable livelihood, decentralized food management, timely response to natural disasters and improving market access for agricultural exports.
Keywords: Public distribution system-India